A Utilization Framework of Ubiquitous Resources for Service Robots Using Semantic Matchmaking. (21st April 2015) - Qian, Kun; Ma, Xudong; Dai, Xianzhong; Fang, Fang; Zhou, Bo
The automatic and flexible utilization of ubiquitous service resources is a key prerequisite for autonomous robots in ambient intelligent environments. In this paper, a novel component-based robotic system (CBRS) framework is proposed in order to support the utilization of task-oriented service resources. In order to increase the reusability of robot control programs and software libraries, a framework that supports semantic modelling, discovery and dynamic selection of ubiquitous services is proposed, which employs semantic services computing technology to facilitate service representations, invocation and interactions. The system architecture is described with an emphasis on the matchmaking method. A new semantic similarity metric is proposed based on an extended OWL relation definition and a matchmaking algorithm is proposed that is compared to the Requirement and Advertisement in ontology using the conceptual span similarity measure. Hence, more reliable semantic matching is achieved compared with previous methods. By developing a rosbridge-based connection management module in the runtime system, the framework is favourable for developing web browser-enabled applications. Experimental results in home-care robot applications validate the effectiveness of the proposed framework.